Some biomorphological peculiarities of peach varieties which determine their photosynthesis productivity (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
The results of comparative studies of leaves` apparatus formation in some peach varieties which belong to the different ecologo-geographical groups and ecotypes have been given. It has been shown that formation of the leaf surface influences on the display of photosynthesis activity of the complex of structures which take part in the initial processes of the light energy transformation. Morphophysiological indexes of the different peach varieties that most objectively characterized photosynthesis productivity depending of variety and ecological properties of their leaves` apparatus have been shared out.
Keywords: leaves` apparatus, ecologo-geographical groups and ecotypes, photosynthesis activity.